Komodifikasi Media dan Dilema Objektivitas: Kajian Sosiologis pada Praktik Jurnalistik Kabar Timur di Ambon - Mahulauw, Syaifulrijal; Tetelepta, Yosina Abigael (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article examines the process of media commodification and the journalistic dilemma of objectivity in Kabar Timur, a local news outlet in Ambon City, using a sociological approach that highlights the tension between market logic and social values. The study aims to analyze how Kabar Timur responds to economic pressures through news commodification practices, and how it balances promotional interests with its public responsibility in delivering information. Employing a qualitative methodology, the research draws on field observation, in-depth interviews with journalists and editors, and content analysis of news products. The findings reveal a hybrid strategy that blends market demands—via advertorial-style reporting—with efforts to maintain balanced and informative narratives to preserve reader trust. The study shows that local media in peripheral regions of Indonesia are not merely passive victims of commercialization, but active, adaptive agents negotiating journalistic professionalism within economic constraints and local cultural frameworks. This article contributes conceptually to the sociology of media by exploring how institutional agency is enacted in the context of global capitalism. Furthermore, it underscores the importance of understanding media dynamics from localized perspectives as a foundation for building more inclusive and context-sensitive media theory. The study recommends strengthening the economic independence of local media without compromising ethical orientation and social function.